Ferroptosis and mitochondrial ROS are central to SARS-CoV-2-induced hepatocyte death - Cevallos, Cintia; Jarmoluk, Patricio; Sviercz, Franco; Freiberger, Rosa Nicole; López, Cynthia Alicia Marcela; Delpino, M. Victoria; Quarleri, Jorge (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAlthough COVID-19 primarily affects the respiratory tract, liver injury has been increasingly reported in infected individuals. The mechanisms by which SARS-CoV-2 induces hepatocyte damage remain poorly understood. Given the role of mitochondrial dysfunction, oxidative stress, and regulated cell death in COVID-19 pathogenesis, we investigated the impact of SARS-CoV-2 infection on hepatocytes using the Huh7.5 cell model.MethodsHuh7.5 hepatocytes were infected with either the ancestral Wuhan (Wh) or Omicron (BA.5) variant of SARS-CoV-2. Viral replication was quantified via RT-qPCR, nucleocapsid protein detection, and infectious particle titration. Mitochondrial function was assessed through mitochondrial membrane potential (ΔΨm), mROS production, and mitophagy analysis. Lipid metabolism and regulated cell death (apoptosis, pyroptosis, ferroptosis) were evaluated by confocal microscopy and flow cytometry. The role of specific cell death pathways was probed using chemical inhibitors.ResultsBoth SARS-CoV-2 variants efficiently infected Huh7.5 cells, with distinct replication kinetics. Infection induced mitochondrial fragmentation, elevated mROS levels, and lipid droplet accumulation. Ferroptosis was identified as a predominant mode of cell death, as evidenced by increased lipid peroxidation and the protective effect of ferrostatin-1. Expression of angiotensin-converting enzyme 2 (ACE2) and transferrin receptor 1 (TfR1), a ferroptosis marker and alternative viral entry receptor, was significantly upregulated post-infection in a variant-dependent manner. Additionally, mROS scavenging with MitoTEMPO impaired viral replication, underscoring the role of oxidative stress in the SARS-CoV-2 life cycle.ConclusionsSARS-CoV-2 disrupts mitochondrial homeostasis and lipid metabolism in hepatocytes, promoting ferroptosis as a major contributor to virus-induced cytopathology. These findings suggest that ferroptosis may play a central role in COVID-19-related liver injury and identify mitochondrial ROS and iron metabolism as potential therapeutic targets.